Influence of slope geometry variations on factor of safety: Comparative analysis of limit equilibrium and finite element method - Merley, Misriani; Joleha, Joleha; Charly Bravo, Wanggai; Faisal, Amsyar; Winda, Fitria; Rama, Gianda; Rendy Fikri, Kurniawan (EDP Sciences, 2025)
Landslides frequently occur in tropical regions with variable topography and rainfall, where slope geometry significantly influences stability. This study analyzes the effect of slope height and angle variations on the Factor of Safety (FS) using two analytical approaches: the Limit Equilibrium Method (LEM) with the Bishop Simplified model and the Finite Element Method (FEM) employing the strength reduction technique. Field measurements were conducted on excavated slopes at the Derofizha Permata Indrapuri Housing Complex, Pekanbaru, characterized by 2.62–4.8 m elevations and 49°–84° slopes under layered soil conditions. Results show that FS decreases with increasing slope height and angle. FEM consistently provides lower FS values than LEM, particularly for slopes higher than 3 m or steeper than 70°, indicating critical to unstable conditions (FS < 1.25). The presence of soft clayey silt layers near the surface further reduces stability. FEM offers more conservative and realistic predictions of potential failure surfaces, while LEM remains effective for preliminary assessments. The findings emphasize the need to integrate geometric variability and soil stratification in slope stability analyses, supporting more reliable risk mitigation and safer housing development in landslide-prone areas.